Management of Northern a Atlantic Bluefin Tuna: the Time Consistency of the Cooperative Management Solution - Brasao, Ana (Nova SBE, 2000)
The purpose of this paper is to examine the stability of the cooperative management agreement of the North Atlantic Bluefin tuna fisheries over time, as the stock recovers, assuming that the players were engaged in previous cooperation for a certain period of time. This analysis is focused on the sharing of the total net returns from cooperation using the concept of Shapley value. It is based on simulation and optimization results from a multi-gear age structured bio-economic model both for the East and the West Atlantic and assumes that the nations were initially in cooperation for either 5 or 15 years. In general terms, the results show, as expected, that the net present values from both cooperation and non-cooperation increase as the stock recovers. Nevertheless, the latter increases more than the former and consequently, the net gains from cooperation decrease. More specific results are obtained for the East and West Atlantic. In the former, it is proved that, the net bargaining power decrease and, as a result, the shares of the net gains from cooperation based on the Shapley Value tend to be equalized, that is, we tend to the Nash bargaining solution. In the latter, the bargaining power may increase and the trend for the equality is not clear. In both, cases there are situations in which the cooperative solution is in the core of the game, meaning that no other strategy yields better outcomes for the players. N/A